HOW COMBINATION OF RETAILER’S RELATIONSHIP EFFORT COULD CREATE LOYAL CONSUMER - RA. Indah Sekar Arum; Asnan Furinto (Journal of Business Strategy and Execution, 2011)
This study develops and empirically tests a model for examination of the impact of different relationship efforts made by a retailer (financial bonding, social bonding, and structural bonding) on key relationship marketing outcomes (trust, relationship commitment, and behavioral loyalty) as relationship duration and product involvement are used as controllable variables in a relationship marketing system. A study in education services from XYZ Company, in Taiwan. The purpose of this study is to test the effects of relationship duration and product involvement, to summarize existing evidence about the behavioral sequences of relationship efforts and relationship outcomes at the individual consumer’s level. The methods of this study use simple linear regression, multiple linear regressions, One‐Way ANOVA, crosstab analysis, descriptive analysis, frequency analysis. Specifically, the results show that relationship duration does have positive influence on consumer behavioral loyalty, and so does product involvement on relationship outcomes. Consequently, managers and employees of retail companies need to be trained, motivated, and rewarded for making relationship efforts to regular consumers.